COVID-19 and human rights - Kjaerum, Morten (London ; New York : Routledge/Taylor & Francis Group, 2021)
"This timely collection brings together original explorations of the COVID-19 pandemic and its wide-ranging, global effects on human rights. The contributors argue that a human rights perspective is necessary to understand the pervasive consequences of the crisis, while focusing attention on those being left behind and providing a necessary framework for the effort to "build back better." Expert contributors to this volume address interconnections between the COVID-19 crisis and human rights to equality and non-discrimination, including historical responses to pandemics, populism and authoritarianism, and the rights to health, information, water access, and the environment. Highlighting the dangerous potential for derogations from human rights, authors further scrutinise the human rights compliance of new legislation and policies in relation to issues such as privacy, protection of persons with disabilities, freedom of expression and access to medicines. Acknowledging the pandemic as a defining moment for human rights, the volume proposes a post-crisis human rights agenda to engage civil society and government at all levels in concrete measures to roll back increasing inequality. With rich examples, new thinking, and provocative analyses of human rights, COVID-19, pandemics, crises, and inequality, this book will be of key interest to scholars, students and practitioners in all areas of human rights, global governance, public health, as well as others who are ready to embark on an exploration of these complex challenges"--
Includes bibliographical references and index.
Keywords: COVID-19 (Disease) -- Political aspects